2014
DOI: 10.1111/caim.12100
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork and Organizational Innovation: The Moderating Role of the HRM Context

Abstract: Evidence is accumulating on the role of teams in shaping a variety of business outcomes, but our knowledge on the effect of teamwork on organizational innovation is still evolving. This study examines whether the extent to which two staff groups are organized in teams (production staff and management/administrative staff) affects organizational innovation and whether human resource management (HRM) systems, which can be of facilitating or constraining nature, enhance the teamwork/innovation relationships. Hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 72 publications
4
77
0
8
Order By: Relevance
“…Innovations at work are a crucial means for organizations to cope with increasing customer expectations, competition, and market dynamics (Anderson, Potočnik, & Zhou, 2014;Fay, Shippton, West, & Patterson, 2015;Subramaniam & Youndt, 2005). …”
Section: Abstract Team Development Innovative Work Behavior Innovatmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovations at work are a crucial means for organizations to cope with increasing customer expectations, competition, and market dynamics (Anderson, Potočnik, & Zhou, 2014;Fay, Shippton, West, & Patterson, 2015;Subramaniam & Youndt, 2005). …”
Section: Abstract Team Development Innovative Work Behavior Innovatmentioning
confidence: 99%
“…That is, innovation development is an interactive process that involves multiple actors with numerous responsibilities who interact to share their problems and ideas, who come up with strategies for realizing their ideas, and who discuss their experiences with prototypes of the innovation in practice (Kanter, 1988;Van der Vegt & Janssen, 2003). Accordingly, to enhance innovation processes, more insight needs to be gained into the dynamics of these social processes that then can be used in organizations to foster the development of innovations (Dyer & Nobeoka, 2000;Singh, 2005).A crucial fact to take into account in this respect is that numerous organizations have adopted work teams as an organizational structure which, if implemented properly, enables efficient work processes (Fay et al, 2015). With respect to the social nature of innovation processes, teams may be expected to contribute to the development of innovations.…”
mentioning
confidence: 99%
“…This contextual condition requires that companies have to be prepared to change permanently, to be flexible and to sense the business environment to achieve a dynamic adaptation to this complex context. For this reason, scholars argue that innovation is the best strategy to allow firms to be more competitive, deal with increasing customer expectations and maintain their position in marketplaces (Fay, Shippton, West, & Patterson, 2015;Hoch, 2013;Shafie, Siti-Nabiha, & Tan, 2014;Subramaniam & Youndt, 2005). Hence, an important theoretical and practical enquiry is to understand how organizations should be led in order to improve their innovation capabilities (Hoch, 2013) making the firms more competitive and more likely to survive in a highly complex business world.…”
Section: Introductionmentioning
confidence: 99%
“…McGuirk et al (2015) showed the importance of innovative HRM on success and performace of small firms. Fay et al (2015) showed the moderating role of HRM on innovative organizations. For this purpose, innovative organizations must develop positive psychological capacities among their employees, both leaders and followers (Toor et al, 2009).…”
Section: Introductionmentioning
confidence: 99%